A 10‐Year Clinical and Radiographic Study of Implants Placed after Maxillary Sinus Floor Augmentation with an 80:20 Mixture of Deproteinized Bovine Bone and Autogenous Bone. (15th October 2012) - Mordenfeld, Arne; Albrektsson, Tomas; Hallman, Mats
Abstract Background There is a need for prospective, long‐term follow‐up studies of implants placed after maxillary sinus floor augmentation (MSFA). Purpose The aim of the present study was to determine whether deprotenized bovine bone (DPBB) used for MSFA may result in long‐term stability of placed dental implants. Material and Methods Fourteen of the 20 patients included in the study were followed throughout the 10 years study period. These patients had 53 implants placed in 22 (6 unilateral and 8 bilateral) maxillary sinuses augmented with a mixture of 80% DPBB and 20% autogenous bone (80:20), and 15 implants placed in non‐grafted sites. Clinical and radiographic examinations of the implants and grafts were performed. Results After 10 years of functional loading 15 of the initially placed 108 implants had been lost giving a cumulative survival rate of 86%. The mean marginal bone loss was 1.6 ± 1.0 mm. There were no statistically significant differences in marginal bone level, pocket depth, or ISQ‐values between implants placed in residual or grafted bone or between smokers or non‐smokers at 10 years follow‐up. There was a statistically significant reduction (p < .01) in graft height between 3 months and 2 years but no further significant reduction up to 10 years. Conclusions The first 2 years after placement of implants with turned surfaces placed in sites after sinus floor augmentation with DPBB and autogenous bone seem to be critical for implant survival. At 10 years follow‐up, the remaining implants presented excellent clinical and radiological results regardless of smoking habits or implant sites (augmented or residual bone).